2004
DOI: 10.1158/0008-5472.can-03-1860
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Stroma Interactions Induce Chemoresistance in Pancreatic Ductal Carcinoma Cells Involving Increased Secretion and Paracrine Effects of Nitric Oxide and Interleukin-1β

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
205
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(219 citation statements)
references
References 31 publications
10
205
0
4
Order By: Relevance
“…Multiple lines of evidence support the link between NO and chemoresistance (47)(48)(49)(50). Herein, we show that O-ASCs regulate cancer cells' response to chemo-drugs through the NO pathway.…”
Section: Discussionmentioning
confidence: 58%
“…Multiple lines of evidence support the link between NO and chemoresistance (47)(48)(49)(50). Herein, we show that O-ASCs regulate cancer cells' response to chemo-drugs through the NO pathway.…”
Section: Discussionmentioning
confidence: 58%
“…considering that plasma galectin-1 levels were elevated from early stages of crc, it is possible that galectin-1 has some relevance to tumor maintenance. recent evidence suggests that the interaction between tumor cells and surrounding stroma plays a critical role in tumor growth, invasion, metastasis, angiogenesis, and chemoresistance (29)(30)(31)(32)(33)(34). It has been shown that galectin-1 regulates cell migration and that galectin-1 binding sites are displayed on cell surfaces in most colon cancer cell lines, while only one of them actually expresses galectin-1 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Using IKKb ablation in myeloid cells in a carcinogen/inflammation model for colorectal cancer, Greten et al (2004) showed that NF-kB controls the ability of invading myeloid cells to produce cytokines, which are involved in promoting tumor growth. In another interesting study, NF-kB appears to mediate an IL-1/nitric oxide paracrine growth loop involving stromal fibroblasts and pancreatic neoplastic cells (Muerkoster et al, 2004).…”
Section: Nf-jb In the Tumor Micro-environmentmentioning
confidence: 94%